2016
DOI: 10.1016/j.tjog.2014.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Impact of clinical audits on cesarean section rate

Abstract: Clinical audits appear to be an effective strategy for reducing the CSR. Therefore, we recommend strict monitoring of the indications in dystocia for cesarean section to reduce the CSR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…They identified high rates of unnecessary and potentially preventable cesarean sections. Another study also showed that a clinical audit is an effective strategy for reducing the cesarean section rate and recommended strict monitoring of the indications for cesarean sections to reduce the cesarean section rate [28]. Therefore, future research needs to consider conducting an audit of the indications for cesarean sections rather than measuring the cesarean section rate alone.…”
Section: Discussionmentioning
confidence: 99%
“…They identified high rates of unnecessary and potentially preventable cesarean sections. Another study also showed that a clinical audit is an effective strategy for reducing the cesarean section rate and recommended strict monitoring of the indications for cesarean sections to reduce the cesarean section rate [28]. Therefore, future research needs to consider conducting an audit of the indications for cesarean sections rather than measuring the cesarean section rate alone.…”
Section: Discussionmentioning
confidence: 99%
“…Best practice rates that have been published for Robson‐1 women are as low as 3% or 6.6%, although most published rates are higher: 12.6 to 23.1%. Other centres have demonstrated that a combination of clear targets, training, and continuous feedback can result in reductions in caesarean section rates without an adverse effect on neonatal outcomes . We have introduced a caesarean section audit in which decision making is analysed retrospectively.…”
Section: Discussionmentioning
confidence: 99%
“…We also identified one paper on benchmarking outcomes for women with hypertensive disorders of pregnancy, which has a similar aim for a different population. There are multiple papers reporting on single goal improvement initiatives regarding both reducing caesarean section rates and reducing OASIS, but these studies look at one specific outcome instead of considering a wider set of outcomes for a particular group of women. We used the ICHOM‐standardized outcome set as an ideal and demonstrated that even without access to all these outcomes, it is possible to identify potential improvements.…”
Section: Discussionmentioning
confidence: 99%
“…Significant between‐hospital variation in CD rates has been documented 6,7 . Audit and feedback of delivery mode rates has become a widely used method of initiating practice changes to improve care by safely reducing CD rates 8‐10 . To date, this strategy has been used exclusively with physicians despite the crucial role of nurses in intrapartum labor management, 11 known variation in nurse‐level CD rates, 12,13 and the American Congress of Obstetricians and Gynecologists recommendation that hospitals review individual CD rates for nurses 14 .…”
Section: Introductionmentioning
confidence: 99%